Analysis of Marketing Management Strategies in Facing Dynamic Consumer Behavior in the Digital Era - Erislan, Erislan (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Consumer behavior in the ever-evolving digital era has become a primary focus for organizations seeking to remain relevant and competitive. This study analyzes effective marketing management strategies in addressing the dynamics of consumer behavior in the digital era. Based on related research and literature, it is found that easy access to information, trust in recommendations from fellow consumers, and the use of mobile devices have become key factors influencing current consumer behavior. To address these challenges, organizations must adopt a consumer-centric approach and leverage information technology to understand consumer preferences and needs. Effective marketing strategies include personalized messaging and content, content marketing, influencer marketing, and user experience optimization. However, the implementation of adaptive marketing strategies also faces challenges, such as a lack of expertise in data analysis and uncertainty in data privacy regulations. Therefore, organizations need to take strategic steps, such as investing in the development of data analysis skills and monitoring the development of data privacy regulations. By implementing adaptive marketing strategies, organizations can enhance consumer engagement, strengthen brand loyalty, and achieve success in an ever-changing business environment.